SAPONIN EXTRACTION FROM INFLORESCENCE OF Musa balbisiana - Hoàng Thị Ngọc Nhơn; Đinh Khánh Diệu; Nguyễn Huỳnh Trâm; Lê Thị Hồng Ánh (HUIT Journal of Science, 2025)
Musa balbisiana is known as a plant rich in nutritional value and has been used in popular medicine for many years. The study aimed to optimize the extraction process to obtain the extract-enriched saponin from the inflorescence of M. balbisiana by the response surface method (RSM). In addition, the bioactive components in the extract were screened. The results showed that M. balbisiana inflorescence extract contained significant amounts of saponins, polyphenols, and flavonoids. The optimal saponin extraction conditions, such as solvent concentration, temperature, and extraction time, are determined by the response surface method (RSM). The saponin content was 56.84 mg/gdm at optimal conditions was 62.41% methanol, the temperature of 65.86 ℃, and the extraction time of 84.81 min.